Sacred Frankincense and Spiritual Meaning in Sasak Muslim Rituals - Hamdani Khaerul Fikri; Abdul Haris Rasyidi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Ritual traditions among Sasak Muslims in Lombok reveal a dynamic interaction between Islamic teachings and ancestral heritage. Specific background: One of the least discussed yet enduring practices is the use of frankincense, which remains controversial among puritan groups but continues to hold deep spiritual value for local communities. Knowledge gap: Previous studies emphasize cultural or syncretic aspects but rarely explore the inner religious experiences and sacred meanings embedded in frankincense use. Aims: This study seeks to uncover the sacredness of frankincense in Sasak Muslim rituals using a phenomenological approach, focusing on meaning, symbolism, and spiritual function. Results: The findings show that frankincense serves as a medium for purification, a channel for prayer, and a symbolic bridge between humans, ancestors, and the Divine, creating an atmosphere of calmness, reverence, and communal cohesion. Novelty: This research offers a new perspective by identifying frankincense as a lived sacred entity within local Islamic spirituality rather than a cultural remnant or superstitious practice. Implications: The study enriches scholarship on Nusantara Islam, strengthens frameworks of religious moderation grounded in local wisdom, and highlights the importance of safeguarding intangible spiritual heritage in contemporary Muslim life. Highlights: Highlights the spiritual meaning and sacred function of frankincense in Sasak Muslim rituals. Reveals how ritual symbols shape inner religious experience and communal harmony. Offers a new phenomenological perspective on lived Islam in local cultural contexts. Keywords: Frankincense, Sasak Muslims, Phenomenology, Ritual Sacredness, Local Islam